Who was Henry VIII? - Labrecque, Ellen; Illustrated by Murray, Jake (New York Penguin Workshop, 2018)
Mainly remembered for his six marriages and his self-appointment as the "Supreme Head of the Church of England," Henry VIII was also attractive, educated, and athletic. When Henry Tudor ascended to the English thrown at the age of 17, his reign looked promising. But by the time of his death in 1547, King Henry VIII was characterized as an extremely egotistical, harsh, and insecure king
Include Illustration and Bibliography
Keywords: Kings and rulers